The alien species Phenolia (Lasiodites) picta (Macleay, 1825) in Sardinia (Coleoptera: Nitidulidae) - Rattu, Roberto; Ruzzante, Giampaolo; Audisio, Paolo; Biscaccianti, Alessandro B (Fragmenta entomologica, 2021)
The Oriental and Eastern Palaearctic species Phenolia picta, recently introduced into some countries of the Mediterranean Basin, including S France and S Italy (Sicily), is here reported for the first time from Sardinia.